Devising a Phonological Awareness Test for Indonesian Children: A Pilot Study. - Wibawati, Restu Wahyu; Woan, Lim Hui; Siswanto, Arif; Rusli, Yazmin Ahmad (Pertanika Journal of Social Sciences & Humanities, 2025)
The few existing phonological awareness (PA) studies in the Indonesian language have mainly concentrated on primary school children. PA in young preschool Indonesian children, particularly those aged below 4, has been neglected. Some aspects of PA, including error patterns and early reading abilities in preschool children, have all been neglected. The potential impact of gender on PA has also not been analyzed. It is essential to develop a PA test for use by professionals (e.g., speech therapists) to identify children with poor PA and to provide early remediation to enable them to cope well later in primary school. This study aims to describe the development process of a newly devised PA test, the Indonesian Phonological Awareness Test (IPAT). The purpose of the study is to propose items that are valid and reliable and to administer them to a small sample of 16 Indonesian children aged 3--6 as a trial before conducting the test on a larger sample size to strengthen its validity. The IPAT comprised two sections: PA tasks (syllable detection, syllable deletion, rhyme detection, rhyme oddity, alliteration detection, phoneme deletion) and reading tasks (letter knowledge, non-word reading, word reading, and sentence reading. The results show that the IPAT is proven to be valid and reliable based on the findings of face validity, content validity, and inter-rater reliability. It can be developed into a standardized screening test to identify the potential risk of reading disorders in Indonesian preschool children. Future studies with larger samples are recommended to strengthen the statistical power of the IPAT.